Intrusion of Out-group/Females in In-group's/Males' Domains and its Consequences in Children's Novel Matilda (Global Journal of Human-Social Science, 2020)
It is very important to form social relations with people in the society. In order to form the social relation with each other, people have to know each other. In order to know each other, people usually utilize the pre-conceived ideas or views about one another without knowing them personally. For instance, women are kind and loving where as men are brave and blunt. This pre-conceived idea about men and women may be faulty because not all women might be kind and loving or not all men might be brave and blunt. If one says that women are kind and loving it may mean that such a person may expect all women to be kind and loving. This stereotypical attitude of a person may lead him/her to behave unjustly to a woman whom he/she finds not loving and kind. With the help of pre-conceived or faulty information, people put the other group of people in different categories. Thus, people have formed different groups in order to judge other people. These groups may be formed on the basis of race, gender, status, power and so on. When the people from a certain group, judge the person as different from their group without knowing him/her personally, they apply their pre-conceived or faulty information; it may lead a clash between the people.